REVITALISASI PERAN KONSELOR DI SEKOLAH - Muhammad Nur Wangid (Paradigma, 2009)
Guidance and counseling in Indonesia’s school had developed for aproximately thirty five years. On those periode the development of guidance and counseling was not always had impact positively. The image of guidance and counseling in school was become dark, and school counselor was considered identical as school police were the kinds of the negatively development. One of the reason was school counselor’s roles had been forgeted, that was school counselor as a counselor, school counselor as a consultant, school counselor as a change agent, school counselor as a primary prevention agent, and school counselor as a manager. Based on those facts therefore the revitalization of the school counselor’s roles, that begun with internal initiative to carry out guidance and counseling proportionally, then strove for the understanding and reforming externally, and to increase school counselor’s skills continually, would improve school counselor’s role that were expected would carry out his roles professionally, so guidance and counseling in school would bright again.Keywords: Revitalization; Scool Counselor’s Roles.